Retail Business "Mitra Serba Ada Stores" In Batam City - Sandy Tio; Dessy Aliandrina (ConCEPt - Conference on Community Engagement Project, 2023)
Currently, more and more business actors are opening convenience store businesses around the Batu Aji area. With so many Department Stores/Retail Businesses in Batam City, it indicates that the level of community needs in Batam City is very large, which causes many business actors to start these businesses. Based on my observations, with the increasing number of competitors emerging at this time, retail business owners must be able to adapt to changes that occur in the market and quickly adapt their business so that it is always in accordance with the needs of the market. And now that technology is growing, business people are starting to venture into the digital world. The name of the Partner of this Job Training activity is the Convenience Partner Store. The Multipurpose Partner store sells various types of goods, starting from stationery, household appliances, electricity, buildings, toys and ice cream, accessories, as well as tools for selling such as plastic bags, styrofoam, rice paper, rice boxes, plastic cups, plastic forks, and also a plastic spoon. The location of Mitra Serba Ada Stores is in the Ruko Mitra Centre Blok. B no. 3,4,5 Batu Aji. The selection of partner locations is very helpful for sales because the Batu Aji area is the most popular sub-district in Batam City. The reason for choosing a Convenience Store as a Practical Work Partner is because the Partner has the potential to be developed even more, marked by an increase in sales turnover every year and a high level of consumer enthusiasm.